New Approaches and Concepts in Intelligence Studies: Actor-Network Theory in the Transformation of Security Intelligence - Mulya, Ade (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
This article examines the fundamental transformations in the study and practice of security intelligence driven by technological convergence, the emergence of non-traditional threats, and the shifting ontology of human-technology interaction. Using the theoretical framework of Actor-Network Theory (ANT) developed by Bruno Latour, this study reanalyzes the intelligence cycle, focusing on recognizing the agency of non-human actors. This approach explicitly rejects the traditional, linear model of the intelligence cycle, which is increasingly inadequate to capture the dynamics of contemporary intelligence. Key findings demonstrate that modern intelligence practice operates as a constantly shifting, heterogeneous network, in which human actors (e.g., analysts, field officers) and non-human actors equally have agency (actancy) and